Rediseño del espacio público e inclusión de un nuevo polideportivo de la quebrada seca del sector sur de Ambato - Tituaña Ugsha, Kevin Giovanny (2024)
This work addresses the design of an urban architectural project that includes the creation of a new sports center and the redesign of the Quebrada Seca linear park in the South Sector of Ambato. Through an exhaustive investigation that covered conceptual, methodological aspects and analysis of references, various needs and problems related to the isolation of public space were identified, such as insecurity and the lack of adequate and community-centered areas. Likewise, limitations were evident in the appropriate spaces for sports practice, both in traditional and emerging sports. The proposal of urban-architectural strategies has led to the creation of spaces that not only fulfill specific functions, but also generate sensations and perceptions, thus contributing to the improvement of well-being, coexistence and social participation in public space. In particular, the architectural design of the new sports center focuses on developing flexible, practical and social environments, with the aim of raising the quality of sports practice in the proposed disciplines. This improvement could translate into a significant increase in skills and effectiveness of sporting activities. Ultimately, it stands out that architecture is positioned as a powerful tool to enhance the quality of life and well-being of the inhabitants, highlighting its positive impact on the community